The Huntington Archive, Digital database collection - The Ohio State University (2006)
[Dt.:] Die Web-Seite der Bildarchivs für Buddhistische und Asiatische Kunst stellt die Sammlung von Schwarzweiß- und Farbdias und Photographie in einer Bilddatenbank zur Verfügung. - [Engl.:] The John C. and Susan L. Huntington Photographic Archive of Buddhist and Related Art contains original colour slides and black and white and colour photographs of art and architecture throughout Asia. This web page provides a pictorial database of the archive's collection.